The External Wealth of Arab Nations : Structure, Trends, and Policy Implications - Mohieldin, Mahmoud; Rostom, Ahmed; Zaki, Chahir (World Bank, Washington, DC, 2020)
The paper makes two main contributions. First, it analyzes net foreign assets and liabilities in selected Arab countries over the past two decades, emphasizing the relative significance of direct versus portfolio investment. It distinguishes between foreign direct investment, portfolio equity investment, official reserves, and external debt. Second, the paper examines the effects of policy variables that affect the accumulation of net foreign assets and its components, analyzing how the existence of a sovereign wealth fund, the country's exchange rate regime, and the development of its financial system affect its net foreign assets. The main findings show that the presence of a sovereign wealth fund is positively and statistically significantly associated with foreign direct investment in Arab countries. Financial development (defined as credit to the private sector as a percentage of gross domestic product) is also statistically significant across various regressions. The more financially developed a country is, the more it should invest in riskier assets, such as portfolio assets. But Arab investors are more risk averse than investors elsewhere. Oil-exporting countries tend to invest more in debt assets than in portfolio assets. For oil-importing countries, financial development is the most important determinant of foreign direct investment.